Electrochemical Behavior of Ni(II)-Salen at the Mercury Electrode - Pércio Augusto Mardini Farias; Margarida Bethlem Rodrigues Bastos (International Journal of Electrochemistry)
The complex Ni(II)-salen has been studied using cyclic and square-wave cathodic stripping voltammetry at the static mercury drop electrode in an aqueous media of phosphate and Hepes buffers (at pH 7.0). The resulting voltammograms consist of a totally irreversible one-electron transfer attributable to the coupling of Ni(II) salen/Ni(I) salen via an EC mechanism. The mean value for the transfer coefficient α in both supporting electrolytes was calculated as 0.35 ± 0.05. The amount of reactant adsorbed after 60 s of accumulation at −700 mV was calculated to be 2.8 × 10−8 mol·cm−2. The detection limit for nickel determination was found to be 3.4 × 10−9 mol L−1.